Chapter 28 Genomics in emerging and developing economies - Gibbon, Sahra (Taylor & Francis, 2018)
Low and middle-income countries have become a site of increasing research interest and investment with the transnational expansion and spread of genomic knowledge and technologies (Kumar 2012, Seguin et al. 2008). This reflects a dynamic terrain in which genomics is being harnessed to address a range of healthcare challenges.